The look of things : poetry and vision around 1900 - Strathausen, Carsten (University of North Carolina studies in the Germanic languages and literatures, 2003)
Examining the relationship between German poetry, philosophy and visual media around 1900, the author argues that the poetic works of Rilke, von Hofmannsthal and George focused on the visible gestalt of language as a means of competing with the increasing popularity of photography and film.